Antidiabetic potential of extracts obtained from different varieties of sorghum - Escobar, Ana Paula (2023)
Type 2 diabetes mellitus is a chronic condition that covers approximately 90-95% of cases. In the current market, there is a wide variety of drugs for its treatment. In recent years there has been a growing interest in alternative approaches such as the use of natural products. There are references about the usefulness of sorghum as a hypoglycemic agent referred to the species cultivated in other regions of the world, but the study of the species adapted to our region (NEA) is of the utmost importance since it is known that they can vary their chemical composition due to edaphoclimatological influences. The objective of this work was to evaluate the hypoglycemic potential of sorghum by measuring the inhibitory capacity of sorghum extracts on the enzyme alpha glucosidase (APG) responsible for glucose absorption at the intestinal level. Samples of red and white variety sorghum were used with 3 different particle sizes for each case, on a 500um sieve (ST500), 500um flour (H500) and 177um fine flour (HF177). The material was macerated for 48h in a previously optimized mixture of solvents, filtered and dried in a rotatory evaporatorThe in vitro APG inhibition assay was performed in a microplate reader using extracts (0.02mg/ml) and acarbose (1mg/ml) as positive control. The final results were expressed as the inhibition ratio in relation to acarbose. It was observed that all the extracts were more active than acarbose (Ir>1). However, the red variety presented greater inhibitory capacity than the white variety. For red sorghum, the most active extract was ST500 (ir=75.68) followed by H500 (Ir= 56.31). In the case of white sorghum, the extract that was most active was ST500 (Ir=46.96) but lower than all the cases of red sorghum. Our findings show that there are significant differences in the hypoglycemic potential of sorghum extracts according to the variety and size of the material used.